Pasteurized milk brand positioning from online social media reviews - Oumolarn , Pacharapol; Ritbumroong, Thanachart (Journal of Applied Statistics and Information Technology, 2022)
Nowadays, effects from technological advance and intense market competition have been forcing all industries need to change their strategies in order to create differences for their goods and services. When firms need to launch new products and services, they usually start from segmentation, targeting and positioning. These processes are fundamental area to make their products and services survive in the intense competition market. This research intent to position 7 pasteurized cow’s milk brands in Thailand. We performed data collective from social network forum, Pantip.com and applied Natural Language Processing technique to tokenize comments and select 500 keywords from them. Keywords were mapped within 8 major milk consuming influence factors by meaning. We generated brand perceptual maps using Multidimensional Scaling from selected keywords. Each map represent brand position by each factor. We also conducted brand perceptual questionnaire for external validation between brand position from survey and forum in comparable form. Finally, using Semantic Network revealed keywords connectivity and insights by using Community Detection. The result of comparable external validation between survey and social media brand perceptual map has QAP Correlation = 0.56 with pseudo p-value = 0.01. Our robustness check method resulted with mostly strong correlation.